Influences of Perceived Medication Necessity, Medication Concern, Side Effects, and Treatment-Time on Inhaled Corticosteroids Adherence in Adult Patients with Asthma - Khamrag, Chatsurang; Wattanakitkrilert, Doungrut; Charoenkitkarn, Vishuda; Dejsomritrutai, Wanchai (Nursing Science Journal of Thailand, 2016)
Abstract Purpose: To study the influence of perceived medication necessity, medication concern, side effects and treatment-time on inhaled corticosteroids (ICS) adherence in adult patients with asthma. Design: A descriptive predictive design. Methods: A purposive sample composed of 120 asthma patients aged between 18 and 60 years who were treated at a tertiary care hospital in Bangkok. Data were collected with Demographic Questionnaire, Health Data Record Form, Medication Adherence Report Scale, Beliefs about Medicines Questionnaire-Specific and Inhaled Corticosteroids Questionnaire-Shortened version. The data were analyzed using descriptive statistics and logistic regression. Main findings: The findings indicated that perceived medication necessity, medication concern, side effects and treatment time could explain 21.1% of the variance in ICS adherence in adult patients with asthma. Medication concern is significant predictors of ICS adherence in adult patients with asthma (p < .05). Conclusion and recommendations: Nurses and health care team should pay attention to evaluate and manage medication concerns in asthma patients. อิทธิพลของการรับรู้ความจำเป็นต่อการใช้ยา ความกังวลจากการใช้ยา ผลข้างเคียง และระยะเวลาการรักษาต่อความร่วมมือในการใช้ยาคอร์ติโคสเตียรอยด์ชนิดสูดในผู้ป่วยผู้ใหญ่โรคหืด บทคัดย่อ วัตถุประสงค์: เพื่อศึกษาอิทธิพลของการรับรู้ความจำเป็นต่อการใช้ยา ความกังวลจากการใช้ยา ผลข้างเคียงและระยะเวลาการรักษาต่อความร่วมมือในการใช้ยาคอร์ติโคสเตียรอยด์ชนิดสูดในผู้ป่วยผู้ใหญ่โรคหืด รูปแบบการวิจัย: การวิจัยเชิงทำนาย วิธีดำเนินการวิจัย: กลุ่มตัวอย่างเป็นผู้ป่วยโรคหืด อายุระหว่าง 18-60 ปี คัดเลือกแบบเฉพาะเจาะจง 120 คน จากโรงพยาบาลระดับตติยภูมิแห่งหนึ่งในกรุงเทพมหานคร เก็บข้อมูลโดยใช้แบบสอบถามข้อมูลส่วนบุคคล แบบบันทึกข้อมูลทางด้านสุขภาพ แบบประเมินความร่วมมือในการใช้ยาคอร์ติโคสเตียรอยด์ชนิดสูด แบบสอบถามความเชื่อเกี่ยวกับการใช้ยาคอร์ติโคสเตียรอยด์ชนิดสูด และแบบสอบถามผลข้างเคียงจากการใช้ยาคอร์ติโคสเตียรอยด์ชนิดสูดวิเคราะห์ข้อมูลด้วยสถิติพรรณนา และถดถอยโลจิสติก ผลการวิจัย : การรับรู้ความจำเป็นต่อการใช้ยาความกังวลจากการใช้ยาผลข้างเคียง และระยะเวลาการรักษาร่วมกันอธิบายความผันแปรของความร่วมมือในการใช้ยาคอร์ติโคสเตียรอยด์ชนิดสูดในผู้ป่วยผู้ใหญ่โรคหืดได้ร้อยละ 21.1 โดยความกังวลจากการใช้ยาเป็นปัจจัยที่สามารถทำนายความร่วมมือในการใช้ยาคอร์ติโคสเตียรอยด์ชนิดสูดได้อย่างมีนัยสำคัญทางสถิติ (p < .05) สรุปและข้อเสนอแนะ: แพทย์และพยาบาลควรให้ความสำคัญกับการประเมินและจัดการกับความกังวลจากการใช้ยาคอร์ติโคสเตียรอยด์ชนิดสูดในผู้ป่วยโรคหืด คำสำคัญ: โรคหืด การรับรู้ความจำเป็นต่อการใช้ยา ความกังวลจากการใช้ยา ผลข้างเคียง ระยะเวลาการรักษา